Rapid and simultaneous analysis of monoiodoacetic acid and inorganic iodine in drinking water by capillary electrophoresis-inductively coupled plasma mass spectrometry - Wu, Yuke; Wang, Xi; Pang, Zhengqin; Zhang, Jinyi; Zheng, Chengbin (Microchemical journal, 2024)
Determination of monoiodoacetic acid and inorganic iodine in drinking water by capillary electrophoresis combined with inductively coupled plasma mass spectrometry. [Display omitted] •A simple method was developed to determination of MIAA and inorganic iodine.•This method is fast, efficient, convenient and environmentally friendly.•It is applicable to monitor the environmental risk of drinking water. Monoiodoacetic acid (MIAA) is a disinfection by-product formed during water disinfection through the oxidation of iodide, followed by a reaction with natural organic matter. It exhibits high toxicity and strong mutagenicity and is potentially carcinogenic to humans. Therefore, the simultaneous detection of MIAA and inorganic iodine can enable the safety assessment of drinking water and expand the study of the dynamic transformation process between the two forms. Currently, there is a lack of efficient and rapid universal screening methods for MIAA and inorganic iodine. In this work, a simple and efficient method was developed to combine capillary electrophoresis with inductively coupled plasma mass spectrometry using a spray-efficient nebulizer interface for the speciation analysis of I− , IO3− , and MIAA. The method is based on qualitative analysis of retention time and quantitative determination using peak area. The detection limits of the three iodine forms were 0.16 μg L−1, 0.40 μg L−1, and 1.22 μg L−1, respectively. By coupling two instruments, the method combines the advantages of rapidity and accuracy with high injection efficiency. It is also more environmentally friendly as it does not require complex pre-treatment and avoids the use of toxic organic compounds. The accuracy of this method has been validated through the incorporation of authentic samples, paving the way for its deployment in the risk assessment of substantial volumes of drinking water and the expansion of the novel approach for further investigation into the genesis and transformation of MIAA.